Distinct microRNA expression profiles in acute myeloid leukemia with common translocations - Li, Zejuan (National Academy of Sciences, 2008)
MicroRNAs (miRNAs) are postulated to be important regulators in cancers. Here, we report a genome-wide miRNA expression analysis in 52 acute myeloid leukemia (AML) samples with common translocations, including t(8;21)/AML1(RUNX1)-ETO(RUNX1T1), inv(16)/CBFB-MYH11, t(15;17)/PML-RARA, and MLL rearrangements. Distinct miRNA expression patterns were observed for t(15;17), MLL rearrangements, and core-binding factor (CBF) AMLs including both t(8;21) and inv(16) samples. Expression signatures of a minimum of two (i.e., miR-126/126*), three (i.e., miR-224, miR-368, and miR-382), and seven (miR-17–5p and miR-20a, plus the aforementioned five) miRNAs could accurately discriminate CBF, t(15;17), and MLL-rearrangement AMLs, respectively, from each other. We further showed that the elevated expression of miR-126/126* in CBF AMLs was associated with promoter demethylation but not with amplification or mutation of the genomic locus. Our gain- and loss-of-function experiments showed that miR-126/126* inhibited apoptosis and increased the viability of AML cells and enhanced the colony-forming ability of mouse normal bone marrow progenitor cells alone and particularly, in cooperation with AML1-ETO, likely through targeting Polo-like kinase 2 (PLK2), a tumor suppressor. Our results demonstrate that specific alterations in miRNA expression distinguish AMLs with common translocations and imply that the deregulation of specific miRNAs may play a role in the development of leukemia with these associated genetic rearrangements.